TANGGUNG JAWAB DEBITUR TERHADAP MUSNAHNYA BENDA JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT BANK - TRISNADEWI, NI MADE (Fakultas Hukum Universitas Dwijendra, 2015)
ABSTRACTÂ Responsibility of debtor to elimination of fidusia warrant goods in credit agreement has connection to bank role as intermediation institute, has function as financial medium in its role, has link between bank and customer based on two connected elements, namely legal and trust. In fact, practically bank in giving credit, warrant is always consideration factor that determine to fulfill credit application from public (debtor).Fidusia originates from word â??fidesâ? means trust. As its meaning, then connection between debtor and creditor represents connection of legal trust. Fidusia giver trust that fidusia receiver will return the warrant that has hand over, after debtor pay full its debt. On the contrary, fidusia receiver trust that fidusia giver will pay fully its debt and will not abuse the warrant in his authority.Â Key Words: Debtor Responsibilities, Fiduciary Assurance,Bank Credit AgreementÂ